Factors affecting early red oak (Quercus rubra L.) regeneration near its northern distribution limit in Quebec - Lebel Desrosiers, Simon; Collin, Alexandre; Bélanger, Nicolas (Frontiers in Forests and Global Change, 2024)
Red oak is an important species within the North American landscape, with climate change projections indicating a potential northward shift in its distribution. However, understanding the factors influencing its regeneration success at the northern limit remains limited. Site conditions and seed provenance adaptability may play critical roles. To bridge this knowledge gap, we conducted a seed transfer study in two northern red oak stands in Quebec. We firstly investigated stand regeneration history through dendrochronological characterization. Then, we monitored the survival and growth of saplings for four red oak provenances across a south-to-north gradient in field and greenhouse settings, with varying soil nutrient levels due to fertilization, and with or without protection from large herbivores. Results indicated that stands have similar age structures with red oak establishment coinciding with the last major fire disturbance in the early 1920s. However, tree species composition and density differed, suggesting differences in fire disturbance regime or ecological succession status prior to fire. Site had the largest influence on red oak regeneration, with the highest tree density and soil water availability site exhibiting a 29 % higher survival rate. Protection against large herbivores also significantly impacted red oak seedling performance, leading to a 16 % higher survival rate. Germination, survival and growth also significantly differed between provenances. The local (northernmost) provenance exhibited the poorest overall performance with 28 to 42 % lower germination, survival and growth rates, while the two southernmost provenances exhibited superior germination and sprout survival. An increase in soil nutrient availability was beneficial to red oak in the greenhouse, but only marginally benefited survival and growth in the field, suggesting that this factor is of less importance than other factors (e.g. water and light availability) for red oak early regeneration. The findings of this study suggest that silvicultural efforts to favor red oak should focus on site and provenance selection, and that water availability is currently limiting red oak regeneration success at acorn and early seedling life stages (i.e. 1 year old seedlings) near its northern distribution limit.